A new generalized Burr XII distribution with real life applications. Issue 3 (3rd April 2021) - Aslam, Muhammad; Usman, Rana Muhammad; Raqab, M. Z.
Abstract: In this paper, a new class for generating lifetime distributions is introduced, called generalized Burr XII (GBXII) family of distributions. Numerous properties of the GBXII distribution are discussed such as probability distribution functions, hazard rate function, and moments. The performance of proposed distribution is compared with many other existing statistical distributions in terms of mean square error and goodness of fit. The applications on the proposed distribution are discussed with the aid of real life examples. The results emphasize that the GBXII distribution can be considered as a competitive model for many other distributions.